The Effects of Ecsotic Program (Education Information Technology-Based Online System) in Increasing the Knowledge, Attitude, and Practices Of Community in Dealing with the Covid-19 Pandemic - R Endro Sulistyono; Sri Wahyuningsih; Nurul Hayati; Achlish Abdillah; Syaifuddin Kurnianto (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
The Covid-19 pandemic has had an impact on society in the fields of policy, religion, social, culture, economy, technology and education. This activity aimed to increase the knowledge, attitude and behavior of the community regarding the COVID-19 pandemic through education information technology-based online system. This study was a quasi-experiment with one group pre-test and post-test design. The activity was carried out four months on three groups, namely children, adolescents, and adults. The planned program was about the dangers of Covid-19, increasing reading literacy and knowledge through posters, memes, and videos about Covid-19, overcoming and preventing Covid-19, providing entrepreneurial skills during the Covid-19 pandemic. The implementation method followed a number of steps: identifying potential and analyzing problems in the community, namely by conducting FGDs with related parties, program design, library research to reference material used during service, making program materials and implementing them through online and offline media by visiting the community. The findings showed that that there was an increase in the level of community knowledge, attitude, and behavior regarding the COVID-19 pandemics. This study found that the community should be approached in different ways based on their developmental stage relating to their ability to receive information.